Pulmonary delivery of flecainide causes a rate‐dependent predominant effect on atrial compared with ventricular depolarization duration revealed by intracardiac recordings in an intact porcine model. (14th September 2018) - de Antonio, Victor Z.; Silva, Anderson C.; Stocco, Fernando G.; Silva, Bruna A.; Marum, Alexandre A.; Bortolotto, Alexandre L.; Belardinelli, Luiz; Verrier, Richard L.
Abstract: Background: Pulmonary delivery of flecainide results in the rapid conversion of atrial fibrillation (AF) to normal sinus rhythm in large‐animal models and is safe and well‐tolerated by normal human volunteers. Objective: We investigated the effects of pulmonary delivery of flecainide on atrial and ventricular depolarization and repolarization duration. Methods: Intratracheal instillation (1.5 mg/kg, rapid push) of flecainide or sterile water (placebo) was performed in 12 closed‐chest, anesthetized Yorkshire pigs with a catheter positioned at the bifurcation of the main bronchi. High‐resolution electrograms obtained from catheters fluoroscopically positioned in the right atrium and left ventricle circumvented measurement errors due to the fusion of P and T waves in surface leads when rapid heart rates shortened the TP interval. Pacing was achieved using electrical stimuli delivered via right atrial catheter electrodes. Results: During sinus rhythm (98 ± 4.7 beats/min), intratracheal flecainide caused comparable ( P = 0.56) increases in atrial depolarization (P a ) duration by 22% (39.8 ± 3.2 to 48.7 ± 3.3 milliseconds) and left ventricular (LV) QRS complex duration by 20% (47.9 ± 1.6 to 57.3 ± 1.8 milliseconds) at peak effect at 2 minutes post‐dosing. During right atrial pacing at 180 beats/min, Pa duration increased by 55% (37.0 ± 2.0 to 57.2 ± 1.6 milliseconds; P < 0.0001). The atrial response was greater ( p = 0.001) than the 30% increase in LV QRS complex duration (46.6 ± 1.7 to 60.6 ± 2.5 milliseconds; P = 0.005). Pa duration and QRS complex duration were unchanged by placebo independent of pacing ( P ≥ 0.4 for both). Atrial repolarization duration (PTa ; P = 0.46) and QTc interval ( P = 0.49) remained unchanged. Conclusion: Intratracheal flecainide exerts a rate‐dependent, predominant effect on atrial compared with ventricular depolarization duration. Pulmonary delivery of flecainide could facilitate AF conversion to sinus rhythm with reduced ventricular proarrhythmia risk.